ANALYSIS OF DETERMINANT FACTORS OF AFFECTING FAMILY ABILITY IN HIGH-RISK PREGNANCY - Ika Mardiyanti; Yasi Anggasari (Nurse and Health: Jurnal Keperawatan, 2021)
Background: The ability of pregnant women to deal with early response to high risks is still below the average, which is one of the causes of complications that can indicate the welfare of the mother and her fetus. Objectives: The aim of this study was to look at the determinants that influence early detection of high-risk pregnancies. Methods: This study used an analytic design with a cross sectional design. The sample size of 112 from a population of 155 was obtained by simple random sampling. The independent variables are individual factors, interpersonal influence, filial value and commitment, while the dependent variable is the family's ability to detect high risk of pregnancy for 3 months, namely August-October 2020 at PMB Ika Mardiyanti. This study uses a questionnaire. Data collection in the form of a questionnaire. Data analysis using SEM-PLS. Results: The results of the significance test concluded that all the path coefficients and the T statistical value of personal factors on interpersonal (0.453; 6.612), interpersonal on filial values ??(0.753; 7.267), filial value for commitment (0.851; 17.048), filial value for ability (0.667 ; 4,679), commitment to ability (0.358; 2.356) is significant. Because all have a T-statistic value that is more than the T-table 1.96. Conclusion: The determinant factors that contribute to the ability of families to detect high risk of pregnancy need to be considered so that families are independent and have efforts to maintain the health of pregnant women in their families. In further research, it is necessary to involve other factors to improve family capacity, especially in the ability of families to detect high-risk pregnancies early.